Peningkatan Keterampilan Berpikir Kreatif Siswa Melalui Model Project Based Learning (PjBL) - Rinia Surya Nita; Irwandi Irwandi (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the effect of the Project Based Learning (PjBL) model through the manufacture of bioplastic preserves on the creative thinking skills of class X students at SMA Negeri 1 Lebong Utara. The method used in this research is Quasi Experiment with Pretest-posttest Control Group Design. The results showed that the Project Based Learning (PjBL) model through bioplastic preserves could improve students' creative thinking skills with a value of 95 and an average of 79.19%. In conclusion, there is an effect of the Project Based Learning (PjBL) model through the manufacture of bioplastic preserves on the creative thinking skills of class X students at SMA Negeri 1 Lebong Utara. Keywords: Creative Thinking, Skills, PjBL